Образ-ікона української хати - Осадча, О. (Інститут народознавства НАН України, 2007)
The article is approaching to some notions and volumes of a term “image”. The image is something much more greater than a picture, it is hyper-real sacral and aesthetic object. Home icons had been painted by folk artists who possessed a sincere faith and endeavour to God. The Ukrainian home icons are embodiments of our people’s being.